Morpho-physiological responses of sea buckthorn (Hippophae rhamnoides) to NaCl stress. (1st November 2020) - Urbinati, G.; Nota, P.; Frattarelli, A.; Lucioli, S.; Forni, C.; Caboni, E.
Abstract: The response to salinity of sea buckthorn, Hippophae rhamnoides, was characterized by treating in vitro growing shoots of the female cv. Leikora with 125 and 250 mM NaCl for 10 and 20 days and evaluating changes in shoot morphology and growth, chlorophyll amount, water content (Wco), proline, total phenols (TPC), quercetin and ellagic acid (EA) contents and in activities of guaiacol peroxidase (G-POD) and ascorbate peroxidase (APX). NaCl treatments reduced growth only at the highest NaCl concentration, relative to the control, and induced a significant decrease of chlorophylls. A significant reduction of Wco and an increase of proline were already observed after 10 days of treatment, regardless of the NaCl concentration applied. TPC content increased as response to 10 days of exposure to the highest salinity and, moreover, a significant increased level of EA was detected, while APX and G-POD activities increased after 20 days of treatment. This study provides a deeper insight into the mechanism of salt response in this species also suggesting a potential role of NaCl in inducing production of bioactive compounds, such as EA.